Perancangan Ulang dan Evaluasi UI/UX Website Stankomdigi Menggunakan Metode System Usability Scale (SUS) dan User Experience Questionnaire (UEQ) - Azzahra Salsabilla; Jaka Septiadi; Ulva Elviani (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2026)
The Stankomdigi website is an official portal that provides various information related to competency standards and human resource development in the digital sector. Preliminary findings indicate several usability issues, including inconsistent layout, less appealing visual design, and suboptimal information presentation. This study aims to redesign the website interface by applying the User-Centered Design (UCD) approach and to evaluate the level of usability and user experience. The research was conducted in four stages: preliminary study, UI/UX design, usability evaluation, and conclusion. The redesigned prototype was evaluated using task-based testing adapted from Cognitive Walkthrough, System Usability Scale (SUS), and User Experience Questionnaire (UEQ), involving 40 respondents. The results show an average success rate of 96.14%, indicating a very high level of system effectiveness in supporting users in completing tasks. Furthermore, the usability measurement using SUS resulted in a score of 73.4, which falls into the “Good” category and is classified as “Acceptable,” indicating that the redesigned system has a good level of ease of use. The UEQ evaluation results show that all dimensions have positive values, with the stimulation dimension achieving an “Excellent” category based on the benchmark. This study contributes by integrating a UCD-based redesign process with comprehensive quantitative validation in the context of a government website, and demonstrates the potential of this evaluation approach for application in the development of similar public service platforms.